Multi-Objective Approach for Optimal DGPV Location and Sizing - A. Syed Mustaffa, S; Musirin, I; M. Othman, M; A. Shaaya, S; K. Mohamad Zamani, M (International Journal of Engineering and Technology, 2018)
The advancement of renewable technology has attracted utility and company to integrate and produce energy for a cleaner environment. The attractive policy from the government also gave the opportunity to adopt the technology recently. The Distributed Generation Photovoltaic (DGPV) integration into the grid is an advanced technology to produce electricity without polluting the environment. Besides providing the green technology, it can also enhance the voltage profile and minimise the transmission losses. However, this depends on the location and the sizing of the DGPV. In this paper, the location and sizing of DGPV are deduced using multi-objective Chaotic Mutation Immune Evolutionary Technique (MOCMIEP) technique. The proposed method determines the optimal location and sizing of DGPV and to improve the losses and FVSI simultaneously. FVSI is a pre-developed voltage stability index based on the line in the power system. The method was tested on the power transmission system of IEEE 30-Bus and IEEE 57 -Bus Reliability Test System (RTS). The results demonstrate the ability of the proposed method to generate the Pareto optimal solutions of the multi-objective problems and come out with the best compromise solution.Â Â